e-Democracy A Group Decision and Negotiation Perspective - Rios Insua, David; French, Simon (Advances in Group Decision and Negotiation ;, 2010)
Web-based interactions to support participation and deliberative democracy, called e-participation and e-democracy, are coming and coming fast. In some instances, the Internet is already permeating politics. However, it is far from clear if the processes involved in these interactions are meaningful and valid, and most of the research in the field has focused largely on the technologies to facilitate or automate the standard democratic instruments involved, such as e-voting or e-debating. This book, though, uses the point of view of the Group Decision and Negotiation approach to thoroughly discuss how web-based decision support tools can be used for public policy decision making. e-Democracy is structured into five main parts. The first part places democracy in context and reviews participatory instruments already in use in the physical world. The second part reviews methodologies that may be used to support groups in public policy decision making with a view on discussing how they may be used in the virtual world. The third part reviews tools already available on the web to support public policy decision making, such as debating, negotiating, voting and supporting decisions; it also identifies their various strengths and weaknesses. The fourth part includes a number of recent case studies, and the final part identifies challenges ahead. Complete with a comprehensive bibliography, this first comprehensive review of e-participation and e-democracy is intended for students, researchers and practitioners in the field as well as researchers in Decision Analysis, Negotiation Analysis and Group Decision Support.